Analysis and prediction models of flow field in mountain tunnels under strong canyon wind. (February 2022) - Chen, Tao; Lu, Zhaijun; Zhou, Dan; Fan, Chuangang
Highlights: Flow structure induced by canyon wind in tunnels with different length analyzed. Vortex dynamics in tunnels was clarified based on the Rankine vortex model. Quantitative prediction models for the flow field in tunnels established. Strong canyon wind should be considered in building pleasant tunnel environments. Abstract: Flow field in mountain tunnels induced by canyon wind, which has significant references for the desirable environment creation in tunnels, has not been fully revealed. In order to investigate the influence of tunnel length on the flow structure and the vortex dynamics in tunnels under strong canyon wind, a series of numerical simulations were performed by using ANSYS Fluent. Numerical models, including the canyon wind domain and the tunnel domain, were established, and the Reynolds-averaged Navier-Stokes (RANS) equations along with the standard k - ε model were validated by model experiments. Nine tunnel lengths (50–2000 m) and six canyon wind velocities (5–30 m/s) were considered. The formation mechanism of the flow structure in tunnels with different lengths was revealed and compared with that in street canyons. Meanwhile, velocity and pressure distributions in the whole tunnel were analyzed based on the Rankine vortex model, the boundary-layer separation and the mass flow rate at tunnel exits. Besides, quantitative models for the flow field in tunnels, which are applicable for typical tunnels with two lanes, were established. This study can be considered as a reference for the pollutant purification and the ventilation system design in mountain tunnels.